Perencanaan Rancangan Mesin Hammer Mill Untuk Proses Produksi Pupuk Organik Dengan Kapasitas 400 Kg/Jam - Dendi Irawan; Antonius F A Silaen (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2020)
Abstract Advances in technology in the industrial era now must be followed by developments that are more effective and efficient. Likewise, the problems that occur in each industrial production process, one of which is the production of palm oil processing (CPO). The problem that occurs is the presence of waste that requires special handling. There are several wastes generated from the processing of oil palm, one of which is the waste of mud and waste of boiler fuel ash. Waste sludge and ash from boiler fuel can be used to become an organic fertilizer. In the process of making fertilizer, it requires tools to make the production process effective and efficient. Hummer mill is a crushing machine for the process of making fertilizers, fertilizer ingredients that are mixed and fermented must be destroyed so that the process of continuing organic fertilizer materials is evenly distributed. Planning a Hummer mill engine design is planned according to needs begins with data collection machine functions so that designing (drawing) engine design and determine some metal materials. Considerations determining the material in accordance with the design and capacity that has been determined and needed. Based on the results of the discussion, the material used is shaft material, iron plate, unp iron, bearing, electro motor, pulley and V-belt as well as filter iron plate. The Hummer mill engine design is designed according to the needs and functions of the final destination of a fertilizer manufacturing process.